Computerized adaptive testing in educational electronic environment of maritime higher education institutions - Olena S. Diahyleva; Igor V. Gritsuk; Olena Y. Kononova; Alona Y. Yurzhenko (Academy of Cognitive and Natural Sciences, 2021)
The article is devoted to the organization of modern learning process, namely the use of innovative technologies - computerized adaptive testing in educational electronic environment of maritime higher education institutions. The example of educational electronic environment is presented in the article on LMS Moodle. The provided new technological and methodological opportunities are a priority in the developed methods of control and testing of knowledge, skills and abilities of students. Comparative characteristic of using computerized adaptive testing in educational electronic environment is given in the article according to different criteria: the role of tests in the learning process; methods of training; equipment; presence of the problems in educational process; level of its control and learning outcomes. The paper also presents examples of activities to form communicative competency of future maritime professionals. Types of adaptive tests are listed in the paper. The research activities were done by second year cadets of ship engineering department of Maritime College of Kherson State Maritime Academy. The experiment was devoted to the formation of communicative competence with the help of electronic environment of maritime higher education institution. The results of experiment proved positive impact of computerized adaptive testing on communicative competence of future ship engineers. Further investigation of adaptive testing can also be done for learning system of maritime education establishments using simulation technologies of virtual, augmented and mixed realities.